The Impact of Taxpayer’s Realization of the Determinants of Applying Value Added Tax on Tax awareness in Saudi Arabia: A Case Study in Tabuk region - Ershaid, Oglah Nawash (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify the impact of taxpayer’s realization of the determinants of applying value added tax on tax awareness in the Saudi Arabia and applied early in 2018. In the light of reviewing the related studies, VAT system, and VAT implementing regulation, a questionnaire about VAT determinants was designed and disseminated to 88 VAT payers in Tabuk region. After analyzing data, this study revealed that applying VAT can be affected by a group of determinants (tax rate, compulsory registration limit, fines, payments, accounting basis, payment method, tax self-censorship, organizational structure of tax administration, learning and training, voluntary registration. This study also revealed that there is a statistically significant effect of taxpayer’s realization of legislation determinants (tax rate, compulsory registration method, fines, payments) and technical determinants (accounting basis, payment method, tax self-censorship) on tax awareness.In light of study results, we recommend to increasing tax knowledge attention, expanding its tools at all school education stages, and increasing the expansion of tax knowledge and dissemination culture at the higher education stage to increase tax awareness.
Keywords: value added tax; determinants of tax application; tax awareness